Compact ultra-wideband antenna for portable devices - Kasi B.; Ping L.C.; Chakrabarty C.K. (Institute of Physics Publishing, 2023)
This article presents a compact ultra-wideband (UWB) antenna for wireless dongle devices. The printed monopole antenna, with the size of 15 mm 30 mm, has an impedance bandwidth ranges from 2.9 to 13 GHz. The proposed structure comprises of a hexagonal radiator fed by a microstrip line with a modified ground plane. Such a design can be easily integrated with wireless universal serial bus (USB) devices. Having stable radiation patterns and constant gain within the UWB spectrum are significant characteristics of this antenna. The time domain studies on the designed antenna indicate reduced ringing effect for impulse excitation across the band of interest. Published under licence by IOP Publishing Ltd.